Erratum for Nagesh et al., phytochemical analysis and docking study of compounds present in a polyherbal preparation used in the treatment of dermatophytosis - Simhadri VSDNA Nagesh; Muthuchamy Muniappan; Iyanar Kannan; Subramanyam Viswanathan (Mazandaran University of Medical Sciences, 2018)
Erratum for Nagesh et al., phytochemical analysis and docking study of compounds present in a polyherbal preparation used in the treatment of dermatophytosis Simhadri VSDNA Nagesh1*, Muthuchamy Muniappan2, Iyanar Kannan3, Subramanyam Viswanathan4 Department of pharmacology Bharath University, Chennai , India Department of Pharmacology, Sree Balaji Medical College and Hospital, Chennai, India Department of Microbiology, Tagore Medical College and Hospital, Chennai, India Department of Pharmacology, Meenakshi Medical College and Hospital, Chennai, India   ERRATUM Volume 3, no. 4, 6-14, 2017, DOI: 10.29252/cmm.3.4.6. This erratum adds the primary affiliation of Simhadri VSDNA Nagesh, a Research scholar. The affiliation line should appear as shown above.